Strategic action fields for German companies in demographic shift. - Su, Guangya (My University, 2019)
Focusing on the 50+ labor force in large companies in Germany, this thesis aims to provide recommendations on how to unleash potential of an aging workforce to continuously deliver value and to ensure a long-term success of companies. The approach employed here is to combine literature analysis and case studies to gain insight, to build a theoretical framework, and to derive recommendations. Two meta-analyses are conducted. The first one is to aggregate age-related differences which are relevant for companies. The second one is to identify potential action ideas and measures. The second case study is an in-depth case analysis within a globally operating German technology company. It includes a review of the company's strategic priorities, top management interviews, an employee survey, and a baselining of workforce structure and existing measures. In addition, research techniques such as statistical data analysis, simulation, and problem-solving method of strategy project management are applied for specific sub research topics. The first result of this thesis is a quantification and qualification of demographic trends in Germany. Secondly, this research identifies fifteen age- or generation-related differences which are relevant for large companies, covering areas of health, learning, and social implication. From a theoretical perspective, the Managing Demography Framework with a measure catalogue is developed. This management framework comprises four action fields: Workforce Composition, Productive Fitness, People Development, and Communication and Culture, with 22 specific action measures in total. The suggestion is to apply the framework in consideration of business context, HR priorities, and evaluation criteria so that measures can be selected and customized for implementation. Finally, from a practical perspective, this research consults the case study company to design its demography program. By applying the Managing Demography Framework for the case study company, it showcases a systematic problem-solving methodology along the situation, implication, and solution process.
Keywords: Arbeitsmarkt; Demographischer Wandel; Arbeitskräfteangebot; Arbeitsmarktpolitik; Wirtschaftspolitik; Arbeitskräftebedarf; Unternehmen; Personalpolitik; Personalplanung; Weiterbildung; Beschäftigter; Qualifikation; Lebensalter; Leistungsfähigkeit; Personalstruktur; Interview; Fallstudie; Älterer Arbeitnehmer; Multinationales Unternehmen; Diversität